THE INVESTMENT IN HUMAN CAPITAL, AN INTRISIC FACTOR OF THE SUSTAINABLE ECONOMIC GROWTH - CRISTINA TEODORA BALACEANU; DIANA MIHAELA APOSTOL (Challenges of the Knowledge Society)
The educational system will need to direct its actions and programs towards the identification of the current and future values of the labour market, starting from the existing and potential labour resources, anticipating first and foremost the adjusting of the economy to fast-developing fields and domains, put forward by the State via the Fast-developing Field Strategies or even via the Fast-developing National Strategy. It will accordingly generate a binder between the demands of the labour market as a response to the developing necessities of the economy, and the training/specialization of the labour force as offered by the national syllabus. By these means the educational system would create a labour force compatible with the labour market, which is both a premiss for the increasing level of employment and for the sustainable economic growth. Our task is therefore to provide a concept of education related to technological progress, based on the model of Nelson and Phelps, and a suggestion for investments and education policies.